DOI: 10.17077/etd.k093ppwx
|View full text |Cite
|
Sign up to set email alerts
|

Nonviral gene delivery to the liver

Abstract: Diseases of the liver have a large impact on human health. Genetic disorders, metabolic disorders, alcoholism, cancer, or infections can all impair liver function. If serious enough, a liver transplant may be necessary, a major surgical procedure which requires lifelong immune suppression and relies on the availability of donor livers. Gene therapy is being intensively studied as a potential method to treat many disorders, including disorders of the liver. While viral gene therapy has seen some success, possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 349 publications
(553 reference statements)
0
2
0
Order By: Relevance
“…RNase H cleavage is the dominant mechanism of antisense oligonucleotide (ASO) therapies, in which a DNA or modified DNA oligonucleotide is delivered that represses translation of a target mRNA through sequence-specific hybridization and subsequent RNase H cleavage and inactivation201 . Previous data from our lab had demonstrated that hydrodynamic dosing of a DNA oligo(T) hybridized to the mRNA poly(A) tail gave equivalent level of expression as dosing mRNA with no poly(A) tail86 , indicating that RNase H was active in vivo after hydrodynamic dosing, in this case to cleave off the poly(A) tail.To prove that RNase H was able to cleave off the tail extensions, SphI (+239) RNA and LU (+5,000) RNA were hybridized with the DNA oligo and incubated with E.coli RNase H. This resulted in distinct bands indicative of RNase H-specific cleavage(Figure 3-7B). The LU (+5,000) mRNA likely had multiple annealing and cleavage points.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…RNase H cleavage is the dominant mechanism of antisense oligonucleotide (ASO) therapies, in which a DNA or modified DNA oligonucleotide is delivered that represses translation of a target mRNA through sequence-specific hybridization and subsequent RNase H cleavage and inactivation201 . Previous data from our lab had demonstrated that hydrodynamic dosing of a DNA oligo(T) hybridized to the mRNA poly(A) tail gave equivalent level of expression as dosing mRNA with no poly(A) tail86 , indicating that RNase H was active in vivo after hydrodynamic dosing, in this case to cleave off the poly(A) tail.To prove that RNase H was able to cleave off the tail extensions, SphI (+239) RNA and LU (+5,000) RNA were hybridized with the DNA oligo and incubated with E.coli RNase H. This resulted in distinct bands indicative of RNase H-specific cleavage(Figure 3-7B). The LU (+5,000) mRNA likely had multiple annealing and cleavage points.…”
mentioning
confidence: 85%
“…Delivery regarding DNA have been reviewed by members of our lab elsewhere 85,86 . This section focuses on the current state of mRNA delivery in the field and how those barriers are overcome (see Figure 1-9 for a summary).…”
Section: Mrna Deliverymentioning
confidence: 99%